2021
DOI: 10.1111/bju.15622
|View full text |Cite
|
Sign up to set email alerts
|

Oncological benefit of re‐resection for T1 bladder cancer: a comparative effectiveness study

Abstract: To quantify the real-world survival benefit of re-resection vs no re-resection in patients diagnosed with T1 bladder cancer (BC) at the population level. Patients and MethodsRetrospective population-wide observational cohort study based on pathology reports linked to health administrative data. We identified patients who were diagnosed with T1 BC in the province of Ontario (01/2001Ontario (01/ -12/2015 and used billing claims to ascertain whether they received re-resection within 2-10 weeks. The time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a Canadian population-based retrospective observational cohort study ( n = 7666), Wettstein et al. ( 15 ) also reported that OS and CSS rates were significantly higher in patients who underwent re-TUR during any time of follow-up. Even after adjusting for background variables, re-TUR was significantly correlated with lower overall mortality (HR 0.88, 95% CI 0.81–0.95, P < 0.001), whereas the details of intravesical treatment were not described in their paper.…”
Section: Discussionmentioning
confidence: 98%
“…In a Canadian population-based retrospective observational cohort study ( n = 7666), Wettstein et al. ( 15 ) also reported that OS and CSS rates were significantly higher in patients who underwent re-TUR during any time of follow-up. Even after adjusting for background variables, re-TUR was significantly correlated with lower overall mortality (HR 0.88, 95% CI 0.81–0.95, P < 0.001), whereas the details of intravesical treatment were not described in their paper.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, reTUR is recommended for all pT1 BCa in clinical guidelines [3]. More recently, Wettstein et al [7] analysed 2162 patients who underwent reTUR among a total of 7666 patients and found that reported that reTUR was significantly associated with lower overall mortality after adjusting for the effects of all assumed confounders (hazard ratio [HR] 0.88, 95% CI 0.81-0.95; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a repeat transurethral resection (reTUR) after initial TURBT is recommended in clinical guidelines [ 3 ]. Indeed, several studies have shown that a reTUR significantly improves recurrence‐free survival (RFS) [ 4 , 5 ], progression‐free survival (PFS) and overall survival (OS) in patients with pathological stage T1 (pT1) BCa [ 4 , 5 , 6 , 7 ]. However, not all the published studies agree on the long‐term oncological value of reTUR [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, second TUR is recommended within 6 weeks for patients diagnosed with HG T1 BCa and HG Ta BCa without the detrusor muscle in the resected samples 4,5,7 . Previous studies showed second TUR plays beneficial roles in treatment, diagnosis, and oncological prognosis 11,12 …”
Section: Advancements In Surgical Concepts Techniques and Devices For...mentioning
confidence: 99%